Evolution of static allometry and constraint on evolutionary allometry in a fossil stickleback. (14th February 2022) - Voje, Kjetil L.; Bell, Michael A.; Stuart, Yoel E.
Abstract: Allometric scaling describes the relationship of trait size to body size within and among taxa. The slope of the population‐level regression of trait size against body size ( i.e . static allometry) is typically invariant among closely related populations and species. Such invariance is commonly interpreted to reflect a combination of developmental and selective constraints that delimit a phenotypic space into which evolution could proceed most easily. Thus, understanding how allometric relationships do eventually evolve is important to understanding phenotypic diversification. In a lineage of fossil Threespine Stickleback ( Gasterosteus doryssus ), we investigated the evolvability of static allometric slopes for nine traits (five armour and four non‐armour) that evolved significant trait differences across 10 samples over 8500 years. The armour traits showed weak static allometric relationships and a mismatch between those slopes and observed evolution. This suggests that observed evolution in these traits was not constrained by relationships with body size, perhaps because prior, repeated adaptation to freshwater habitats by Threespine Stickleback had generated strong selection to break constraint. In contrast, for non‐armour traits, we found stronger allometric relationships. Those allometric slopes did evolve on short time scales. However, those changes were small and fluctuating and the slopes remained strong predictors of the evolutionary trajectory of trait means over time ( i.e . evolutionary allometry), supporting the hypothesis of allometry as constraint. Abstract : Phenotypes of a weakly armored Threespine Stickleback, Gasterosteus doryssus, with two dorsal spines and a vestigial pelvis (above) and a strongly armored G. doryssus with three dorsal spines, a full pelvis, and two pelvic spines (below; first dorsal spine is indicated by an impression).